Interaction of smoothened with integrin‐linked kinase in primary cilia mediates Hedgehog signalling. (23rd July 2013) - Barakat, Badia; Yu, Liang; Lo, Camden; Vu, Duc; De Luca, Elisabetta; Cain, Jason E; Martellotto, Luciano G; Dedhar, Shoukat; Sadler, Anthony J; Wang, Die; Neil Watkins, D; Hannigan, Gregory E
Abstract : Here we report that ILK localizes in the mouse primary cilium, a sensory organelle required for signalling by the Hedgehog (Hh) pathway. Genetic or pharmacological inhibition of ILK blocks ciliary accumulation of the Hh pathway effector smoothened (Smo) and suppresses the induction of Gli transcription factor mRNAs by SHh. Conditional deletion of ILK or Smo also inhibits SHh‐driven activation of Gli2 in the embryonic mouse cerebellum. ILK regulation of Hh signalling probably requires the physical interaction of ILK and Smo in the cilium, and we also show selective cilia‐associated interaction of ILK with β‐arrestin, a known mediator of Smo‐dependent signalling. Interaction of smoothened with integrin‐linked kinase in primary cilia mediates Hedgehog signalling: The protein kinase ILK promotes the movement of Smoothened into the mouse primary cilium and is required for the induction of Gli transcription factors in response to Sonic Hedgehog.